2020
DOI: 10.1016/j.ejon.2020.101845
|View full text |Cite
|
Sign up to set email alerts
|

Fear of cancer recurrence following allogeneic haematopoietic stem cell transplantation (HSCT) for haematological malignancy: A cross-sectional study

Abstract: The aim of this study was to quantify the prevalence of Fear of Cancer Recurrence (FCR) in patients with a prior haematology malignancy surviving more than one year post allogeneic haematopoietic stem cell transplantation (HSCT), and to identify the demographic, medical and psychological factors associated with FCR occurrence. Method: Participants were adult allogeneic HSCT recipients who had undergone the procedure for acute leukaemia or other haematological malignancy between the years 2000-2012 in Sydney, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Study characteristics are described in Table 1 [30–99] . Dates of publication included 1990 to 1999 (4%); 2000 to 2009 (11%); 2010 to 2015 (34%); 2016-April 2021 (49%), with research being conducted internationally, most commonly the United States (47%), Canada (9%), Netherlands (10%), and Australia (9%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study characteristics are described in Table 1 [30–99] . Dates of publication included 1990 to 1999 (4%); 2000 to 2009 (11%); 2010 to 2015 (34%); 2016-April 2021 (49%), with research being conducted internationally, most commonly the United States (47%), Canada (9%), Netherlands (10%), and Australia (9%).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty percent of associations were contained within interventions for late effects (45/150) and 5% of associations were in the other category. Brice et al, 2020 [38] Austraila N = 1475 Hematolgic PT C FCR: Fear of Recurrence Scale 22/22 10 Burstein et al, 1999 [39] USA N = 480 Breast PD C FCR: Fear of Recurrence Index 20/22 11 Cameron et al, 1998 [40] USA N = 140 Breast PT L Worry: (3 items) 13/28 12 Cannon et al, 2011 [41] USA N = 551 Mixed PT L Worry: (3 items) 22/22 13 Champagne et al, 2018 [42] Canada N = 962 Mixed PD L FCR: FCRI-SF 20/22 14 Charlier et al, 2012 [43] Belgium N = 464 Breast PT C Worry: (1 item) 15/22 15 Chipperfleld et al, 2013 [44] Australia N = 356 Prostate PT C Anxiety: HADS 22/22 16 Choi et al, 2019 [45] USA N = 52 Lung PD C Anxiety: STAI; Worry: cancerrelated worry questionnaire 14/22 17 Cillessen et al, 2020 [46] Netherlands N = 125 Mixed PD RCT FCR: FCRI 21/24 18 Cohen et al, 2018 [47] Canada N = 84 Head and neck PD L Anxiety: Structured Clinical 21/22 19 Davies et al, 2018 [48] UK N = 380 Melanoma PT C Interview Anxiety: HADS 21/22 20 DosSantos et al, 2019 [49] France N = 129 Mixed PD L Anxiety: STAI-Trait 22/22 21 Dunne et al, 2019 [50] Ireland [60] Netherlands N = 2620 Colorectal PD C Anxiety: HADS 21/22 32 Iyer et al, 2016 [61] USA N = 204 Cervical PT L Anxiety: PROMIS-SF 21/24 33 James et al, 2018 [62] USA N = 56 Mixed PD L Anxiety: HADS 16/22 34 Kasparian et al, 2012 [63] Europe Keyzer-Dekker et al, 2012 [66] Netherlands N = 151 Breast PD C Anxiety: STAI 22/22 38 Kowalkowski et al, 2014 [67] USA N = 109 Bladder PD C FCR: (5 items) 22/22 …”
Section: Fear Of Cancer Recurrence and Related Constructs: Relationsh...mentioning
confidence: 99%
“…In another cross-sectional study, Brice et al. 39 analyzed 364 HSCT survivors and found that about 11% of the respondents lived with severe FCR, while only 5% exhibited no FCR. The contrasting findings between our study and their study may be attributed to the different FCR assessment tools employed, as well as differences in HSCT survivors recruited.…”
Section: Discussionmentioning
confidence: 99%
“…The larger study sought detailed information about the late consequences of HSCT, their relationships to various sociodemographic and transplant variables, and the effects these had on Australian survivors’ experiences and QoL. The data collected were analyzed by topic and published in appropriate target journals ( Brice et al, 2017 , 2020 ; Dyer, Brice, Gilroy, et al, 2018 ; Dyer, Brice, Schifter, et al, 2018 ; Dyer, Gilroy, et al, 2016 ; Dyer, Larsen, et al, 2016 ; Gifford et al, 2016 ; Lindsay et al, 2016 ; Smith et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%